2018
DOI: 10.1007/s00592-018-1159-2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to special diets and its association with meeting the nutrient recommendations in individuals with type 1 diabetes

Abstract: Special diets are frequently followed by individuals with type 1 diabetes. The adherents are more frequently women, and have longer diabetes duration and more diabetes complications. Achieving the dietary recommendations differed between diets, and depended on the nutrient in question. Overall, intakes of fibre, vitamin D, folate, and iron fell short of the recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
0
13
0
8
Order By: Relevance
“…While exercise is a known modulator of GE, this study provides novel insight into the impact of the interaction of diet and exercise on GE. Recently, Ahola et al reported that people with diabetes for longer duration are more likely to follow special diets (such as vegetarian, protein restriction etc.,) (29) . There is a clinical need to improve our understanding of the interaction between diet and exercise so that we can explore the effect these special diets may have on glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…While exercise is a known modulator of GE, this study provides novel insight into the impact of the interaction of diet and exercise on GE. Recently, Ahola et al reported that people with diabetes for longer duration are more likely to follow special diets (such as vegetarian, protein restriction etc.,) (29) . There is a clinical need to improve our understanding of the interaction between diet and exercise so that we can explore the effect these special diets may have on glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, patient adherence to the recommended diet seems to be gender-specific. For example, Ahola et al [40] assessed frequency of adherence to special diet in a large cohort Finnish DN study and reported that adherents were more frequently women, older, and had longer duration of diabetes. Therefore, effective adherence through patient education may be a crucial factor in the management of DN through diet.…”
Section: Diet Therapy In Diabetic Nephropathy and Its Importancementioning
confidence: 99%
“…DM management needs to integrate the drug therapy [5], diet [6,7], exercise [7,8], and possible complementary treatments [9]. The successful management of DM is influenced by lifestyle [7,9], includes eating habits [4,6,7]. Most of the world's population has eating habits using easily absorbed foods, rich in carbohydrates, low in fiber, and resistant starch (RS), such as rice.…”
Section: Introductionmentioning
confidence: 99%
“…It can contain high RS and highfiber ingredients. Former studies reported that high-fiber diet could improve blood glucose control and attenuate hyperinsulinemia in DM type 2 patients [6,11]. Therefore, this study was to analyze the mechanism of blood glucose improvement after AR consumption in diabetic rat model.…”
Section: Introductionmentioning
confidence: 99%